Collaboration, campaigns and champions for appropriate imaging: feedback from the Zagreb workshop - D. Remedios; B. Brkljacic; S. Ebdon-Jackson; M. Hierath; V. Sinitsyn; J. Vassileva (Insights into Imaging, 2018)
Abstract Leading radiologists and representatives from national radiation protection regulatory authorities and health ministries from 19 countries of the European region worked together with five experts at the workshop on justification and appropriate use of imaging in Zagreb, Croatia, from 26 to 28 October 2017 jointly organised by the IAEA and the European Society of Radiology. The workshop served as a forum to exchange information on challenges and solutions for improving justification and the appropriate use of diagnostic imaging. Common barriers to improving the use of imaging referral guidelines were discussed and the need for increased collaboration identified. Examples of good practices were presented, including use of Clinical Decision Support (CDS) systems to facilitate rapid and good justification decisions. The workshop identified some of the needs of European countries for achieving more appropriate imaging proposing wider use of collaboration, campaigns and champions. Main messages • Drivers for appropriate imaging in Europe are similar to those elsewhere globally. • Implementing imaging referral guidelines is the main barrier to more appropriate imaging. • Clinical Decision Support systems (CDS) facilitates good referral practice and justification decisions. • Collaboration, campaigns and champions may improve awareness, appropriateness and audit.